다빈도 한약 처방 10종에 대한 혈관 평활근 이완 효과 - 김범정; Bumjung Kim (大韓本草學會誌, 2025)
Objectives : Hypertension, a chronic disease with a high incidence rate, is a major disorder accompanied by various complications and can lead to death in severe cases. In addition to taking antihypertensive drugs, various complementary therapies are being utilized, and the importance of managing hypertension through the use of herbal medicine is gradually being highlighted. In this study, we evaluated the vasorelaxant effects of 10 Korean Herbal Formulas (KHF) on the rat thoracic aorta constricted with potassium chloride (KCl). Methods : The KHF were extracted by reflux cooling at 100℃ for 2 hours after adding distilled water 10 times the weight of each sample. To investigate their vasodilatory potential, the thoracic aorta from the rat was isolated and mounted in an organ bath containing 10 ml of modified Krebs-Henseleit (KH) buffer. Contractions were induced by the addition of KCl, and then the vasorelaxant effects of increasing concentrations (10-1,000 μg/ml) of KHF extracts were assessed. Results : Among the 10 KHF, Oyaksungi-san, Yijung-tang, and Cheonwangbosim-dan showed vasorelaxant effects. And Banhabakchulcheonma-tang, Bangpungtongseong-san, Samso-eum, Samchulgeonbi-tang, Yijin-tang, Jaeumganghwa-tang, and Hyangso-san showed no significant vasorelaxant effects. Furthermore, when administered concurrently with amlodipine, Cheonwangbosim-dan enhanced the vasorelaxant effects compared to amlodipine used alone, conversely, Samso-eum attenuated the vasorelaxant effects of amlodipine. Conclusion : These findings are expected to contribute valuable data towards establishing guidelines for the combined use of KHF and Western antihypertensive drugs in hypertension treatment.